PECTINAMETILESTERASE EM EXTRATO DO ALBEDO DE MARACUJÁ-AMARELO (Passiflora edulis f. flavicarpa) - Meneguzzo, Adeline Chaicouski (2014)
The pectic substances, carbohydrates found in plant cell wall, are involved in the change of texture in the ripening process under action of pectinolytic enzymes, among which pectinmethylesterase. The production and consumption have increased the passion, also indicating an increase in the amount of waste generated, among which the albedo. The objective of this study was to evaluate the enzymatic activity of the crude extract obtained pectinametileserase albedo yellow passion fruit. The sequence of experiments was to determine the extraction protocol of the enzyme and characterization of the enzyme activity in the crude extract obtained from the albedo of yellow passion fruit, as the stage of maturation, NaCl concentration and substrate storage time, pH and temperature. When comparing the level of passion fruit in green and ripe, fresh and lyophilized maturation, the best result was found in green lyophilized samples. Among the five extraction methods used, two of them stood out and were adapted, and made the triple rinsing the material with cold water to remove soluble substances, followed by extraction with pectinmethylesterase PVPP and NaCl. The best salt concentration for higher activity obtained with NaCl 1,0 mol L- 1, both in the extraction, as in the determination of pectin methyl esterase activity. The best substrate concentration found was 1,0 % citrus pectin. The influence of the storage period of raw material showed that the freeze-dried fruit enzyme activity remained for a longer period, followed by the frozen sample and then refrigerated. The optimum pH was found to be 8 and the optimum temperature of 50 °C. The enzyme was heat-stable. The ideal range of precipitation with ammonium sulphate was 40-60 % of the salt. With the studies was possible to detect and study the pectinmethylesterase in extracts obtained from samples of albedo yellow passion fruit, with influence of various factors such as salt concentration and pH.